Mitos dalam Tradisi Mowang Na’as Masyarakat Desa Penambangan Kabupaten Bondowoso - Dyna Indani (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study is to describe the problems related to the Mowang Na'as myth, the function of the Mowang Na'as myth, and the cultural values of the Mowang Na'as myth. The myth of Mowang Na'as is interesting to study because it contains local wisdom and is an interesting phenomenon in the Mining Village of Bondowoso Regency. This type of research is qualitative research with Spradley's ethnographic research design. This research data presents information related to the Mowang Na'as myth which starts from raw data and is processed into information. The data source of this research consists of several informants who live in Penambangan Village. Data collection and this research used observation, interview and translation techniques. The results of this study include the form of the Mowang Na'as myth in the form of its origin story. The functions obtained are providing safety and welfare for the people of Penambangan Village, Bondowoso Regency, preserving traditions and strengthening social ties. Cultural values include religious values, social values, and personality values. As well as an alternative teaching material for learning Indonesian folklore texts in secondary schools. It is expected that further research will focus more on more complex information about the myth of Mowang Na'as
Reaploud Repository Hasyim April 2026
Keywords: Mowang Na'as; Myth; Function; Cultural Value; and Education